Post-Acute COVID-19 Syndrome: a 12-month telemonitoring cohort to assess the persistent symptoms and the quality of life (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2025)
Introduction: After the end of the COVID-19 pandemic, another colossal challenge continues to be faced by the health system worldwide: the post-acute COVID-19 syndrome. Objectives: This study aimed to evaluate respiratory symptoms and QoL (quality of life) in a cohort of previously hospitalized COVID-19 patients after twelve months of discharge. Additionally, the study aimed to identify clinical factors related to these symptoms. Methods: This longitudinal study, with a 12-month cohort, was conducted with adults discharged home after hospitalization for COVID-19. Twelve months post-discharge, the participants were assessed through video or phone calls and answered a questionnaire regarding persistent symptoms and QoL. The modified Medical Research Council scale (mMRC) was used to grade the impact of dyspnea on daily activities, and the WHOQoL-BREF questionnaire was used to assess the QoL. Results: The cohort included 15 patients, with a mean age of 63.53±7.32 years. Twelve months after discharge, 10 (66.66%) individuals suffered from at least one symptom, among which 40% reported cough, 20% reported fatigue, 20% had dyspnea at rest, and 40% had dyspnea during activities. The physical domain of QoL had the lowest score (9.14±3,54) among the WHOQoL domains. Age, sex, diabetes, and mMRC≥1 correlated with QoL. Conclusion: The high prevalence of respiratory symptoms and impaired QoL even 12 months after hospital discharge highlight the need to adopt protocols for in-hospital rehabilitation and prepare patients for practice physical activity or exercise-based rehabilitation programs after discharge.
Keywords: Post-Acute COVID-19 Syndrome; COVID-19; SARS-CoV-2; Quality of life; Telemonitoring